Ecological status assessment in mediterranean rivers: complexities and challenges in developing tools for assessing ecological status and defining reference conditions - Dallas, Helen F. (Hydrobiologia, 2013)
Rivers in mediterranean regions are subject to hydrological extremes. They range from highly stable, perennial ground- or snow-fed systems to highly ephemeral, unpredictable ones in semi-arid environments. Spatial and temporal complexity inherent in these systems presents challenges for ecological status assessment and defining reference conditions, particularly as many areas have been extensively transformed through anthropogenic activities. Temporal variability driven by sequential and predictable, seasonal events of flooding and drying accentuates the need to take season and/or hydrological period into account. Intermittent streams, which are common in mediterranean regions (med-regions) and which have aquatic communities distinct from perennial streams, are often not incorporated in bioassessment and present distinct challenges. Med-regions are also known for their high biodiversity and rates of endemism, as well as large numbers of introduced species. Med-regions are expected to be among the most affected by global climate change and, in these systems, climate change is an additional driver influencing ecosystems that are already stressed. From this review it is evident that an understanding of responses of indices, metrics, and models to climate change in comparison to existing stresses, and the development of thermally specific bioassessment tools are needed for this region.